Increasing dark adaption times and ERG response in landrace pigs - an intraindividual comparison in 20 animals - Ackermann, Bryan Calder; Skrzypczyk, Lea; Geisweid, Ludwig; Junker, Niklas; Wohlfart, Sabrina; Uhl, Philipp; Auffarth, Gerd U.; Augustin, Victor A.; Hammer, Maximilian (Experimental eye research, 2026)
Purpose - To evaluate the influence of different dark adaptation (DA) times on full-field electroretinogram (ff-ERG) responses in pigs, establish baseline reference data, and assess the suitability of the porcine eye as a translational model for human retinal physiology. - Methods - In this intraindividual study, ff-ERGs were recorded from the left eyes of 20 male German Landrace pigs following ≥25, 15, 10, 5, and 0 min of dark adaptation using standard ERG protocols (LA 3.0, Flicker, DA 0.01, DA 3.0, DA 10.0) compliant with the International Society for Clinical Electrophysiology of Vision (ISCEV). Amplitudes and latencies of a-waves, b-waves, and oscillatory potentials were analyzed using repeated-measures ANOVA with Dunnett's post hoc comparisons. - Results - Amplitudes, particularly in rod-isolated responses (DA 0.01), significantly decreased with shorter DA times (≥15 min vs. 0 min: mean difference in b-wave amplitude = 86.81 μV, p < 0.0001). Mixed rod-cone responses (DA 3.0, DA 10.0) were moderately affected, while oscillatory potentials remained stable. Latency changes were partially statistically significant but remained below a difference of 5ms. These findings mirror human data where shorter DA times reduce amplitudes, especially for weak stimuli, without altering waveform morphology. - Conclusions - ERG responses in pigs to varying DA times closely parallel human retinal physiology, particularly in the sensitivity of rod-mediated responses to short adaptation. This underscores the translational value of the pig model in preclinical retinal research and highlights the need for standardized DA times to ensure reproducibility. A 10-min DA may suffice for strong-flash protocols, while ≥25 min is recommended for rod-isolated testing.